2022
DOI: 10.1186/s12877-021-02656-2
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of clinical effectiveness of self-management interventions in Parkinson’s disease

Abstract: Background Parkinson’s disease is a complex neurodegenerative condition with significant impact on quality of life (QoL), wellbeing and function. The objective of this review is to evaluate the clinical effectiveness of self-management interventions for people with Parkinson’s disease, taking a broad view of self-management and considering effects on QoL, wellbeing and function. Methods Systematic searches of four databases (MEDLINE, Embase, PsycIN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 69 publications
0
35
0
Order By: Relevance
“…While a holistic, multidisciplinary approach is desirable, a minority of patients have access to such care. Qualitative research suggests that many healthcare professionals consider self-management in Parkinson's disease as important but identify barriers such as lack of resources [8], and research in this field is currently limited [9]. Face-to-face self-management courses are available through charities and peer-support.…”
Section: By Heather Angus-leppan Alice Caulfield Melika M Moghim Jenn...mentioning
confidence: 99%
“…While a holistic, multidisciplinary approach is desirable, a minority of patients have access to such care. Qualitative research suggests that many healthcare professionals consider self-management in Parkinson's disease as important but identify barriers such as lack of resources [8], and research in this field is currently limited [9]. Face-to-face self-management courses are available through charities and peer-support.…”
Section: By Heather Angus-leppan Alice Caulfield Melika M Moghim Jenn...mentioning
confidence: 99%
“…Most research on self-management has focused on chronic conditions such as arthritis and diabetes [10]; however, there is a growing focus on Parkinson's [11,12]. Parkinson's self-management includes adherence to medication regimes, exercising, diet management, the monitoring of various symptoms, and management of environmental factors [13].…”
Section: Introductionmentioning
confidence: 99%
“…Parkinson's self-management includes adherence to medication regimes, exercising, diet management, the monitoring of various symptoms, and management of environmental factors [13]. A systematic review exploring the effectiveness of self-management interventions found mixed results due to small and poor-quality studies [11]. However, components more frequently observed in effective interventions were information about resources; training or rehearsing psychological strategies; social support; and lifestyle advice and support.…”
Section: Introductionmentioning
confidence: 99%
“…In a systematic review of self-management interventions in people with Parkinson’s, only 4/36 studies showed a significant improvement for quality of life in the intervention arm. 7 To understand any lack of effect following a trial, a fidelity assessment is needed to determine if the intervention was delivered as planned in the protocol. This review will focus on two subcomponents of a fidelity assessment: fidelity of intervention delivery and fidelity of engagement.…”
Section: Introductionmentioning
confidence: 99%
“… 10 This ensures that when interventions are implemented, these core components are emphasised, so effects seen in trials are translated into clinical care. However, in the Walton et al 9 review of complex health behaviour change interventions, only 36% measured fidelity and engagement; the review by Pigott et al 7 found none of the included studies conducted a formal fidelity assessment, and reviewing implementation fidelity for self-management for osteoarthritis, Toomey et al 11 found very low fidelity reporting, with only 1/22 studies achieving acceptable reporting levels.…”
Section: Introductionmentioning
confidence: 99%